Molecular diagnosis of maturity‐onset diabetes of the young in a cohort of Chinese children. Issue 3 (28th January 2020) - Xu, Aijing; Lin, Yunting; Sheng, Huiying; Cheng, Jing; Mei, Huifen; Ting, Tzer Hwu; Zeng, Chunhua; Liang, Cuili; Zhang, Wen; Li, Cuiling; Li, Xiuzhen; Liu, Li
Abstract: Objective: The purpose of this study was to investigate the molecular basis of maturity‐onset diabetes of the young (MODY) by whole‐exome sequencing (WES) and estimate the frequency and describe the clinical characteristics of MODY in southern China. Methods: Genetic analysis was performed in 42 patients with MODY aged 1 month to 18 years among a cohort of 759 patients with diabetes, identified with the following four clinical criteria: age of diagnosis ≤18 years; negative pancreatic autoantibodies; family history of diabetes; or persistently detectable C‐peptide; or diabetes associated with extrapancreatic features. GCK gene mutations were first screened by Sanger sequencing. GCK mutation‐negative patients were further analyzed by WES. Results: Mutations were identified in 24 patients: 20 mutations in GCK, 1 in HNF4A, 1 in INS, 1 in ABCC8, and a 17q12 microdeletion. Four previously unpublished novel GCK mutations: c.1108G>C in exon 9, and c.1339C>T, c.1288_1290delCTG, and c.1340_1343delGGGGinsCTGGTCT in exon 10 were detected. WES identified a novel missense mutation c.311A>G in exon 3 in the INS gene, and copy number variation analysis detected a 1.4 Mb microdeletion in the long arm of the chromosome 17q12 region. Compared with mutation‐negative subjects, the mutation‐positive subjects had lower hemoglobin A1c and initial blood glucose levels. Conclusions: Most MODY cases in this study were due to GCK mutations, which is in contrast to previous reports in Chinese patients. Diabetes associated with extrapancreatic features should be a clinical criterion for MODY genetic analysis. Mutational analysis by WES provided a precise diagnosis of MODY subtypes. Moreover, WES can be useful for detecting large deletions in coding regions in addition to point mutations.